PELAKSANAAN PENGAWASAN KUALITAS SEKOLAH OLEH UNIT PELAKSANA TEKNIS DINAS (UPTD) PENDIDIKAN DI SMA NEGERI 3 PINGGIR KECAMATAN PINGGIR KABUPATEN BENGKALIS - Sarianti Sarianti; Ahmad Tarmizi Yusa (UIR Press, 2018)
This study aims to determine the Implementation of School Quality Supervision by Technical Implementation Unit of the Office (UPTD) Education in SMA Negeri 3 Pinggir Pinggir Sub-district Bengkalis District. Implementation Monitoring Indicators used include student standard and achievement in schools, performing quality of student services in schools and school management leadership Implementation of School Quality Supervision by Technical Implementation Unit of Education Office at SMA Negeri 3 Pinggir Kecamatan Pinggir Kabupaten Bengkalis. The type of research located in the Technical Implementation Unit of the District Education Office (UPTD) in Sub-district Pinggir is Descriptive Survey because this research aims to explain explain, and describe the reality. There are 4 groups of population and sample in this research that is, Head of UPTD which amounts to 1 person, supervisor coordinator which amounted to 1 person, Oversight Auditor amounted 3 0rang and Guru amounting to 5 people. Sampling technique used is using purpose technique. Types and data collection techniques consist of primary data collected by using questionnaire and interview data and secondary data collected by observation and documentation technique which is the source of data and information and information from the parties related to this research. Based on this analysis technique can be concluded that the Implementation of School Quality Supervision by Technical Implementation Unit of Education (UPTD) of Education in SMA Negeri 3 Pinggir Kecamatan Pinggir Bengkalis run with Effective Enough. Recommendations that need to be considered especially with respect to the implementation of supervision that must be optimized in order to create capable of quality schools.